Corporate Establishments preferences and the guest for overseas qualification by Nigerian university students (2009)
This study examines corporate establishment demand as the quest for foreign education in Nigeria and seeks to expose the motivation behind the rush abroad for foreign education; explicated by the increasing level of university seekers within and outside Nigeria. A combination of quantitative and qualitative research methodology was adopted for this study. Major findings revealed that employers of labour demand for foreign certificates holders over national certificates holders. Among the sampled respondents, the effect of certificates acquired abroad on the nation’s industries has declined. It was also observed that free-tuition institutions have increased students rush to study abroad irrespective of the courses being offered. Based on these findings, it is suggested that there is the need for government to reform the Nigerian educational system; to eliminate the discrimination on employment based on foreign degrees, as well as families to reorient their wards on courses being offered abroad.